Development of an Air-controlled Futon with an In-bed Temperature Feedback Function - MAKIKAWA, Masaaki; SUZUKI, Shingo; KURODA, Shohei; FUJIWARA, Yoshihisa; IIDA, Takeo; YASUDA, Masashi; OKADA, Shima; MATSUURA, Hidefumi (Transactions of Japanese Society for Medical and Biological Engineering, 2004)
In this study, we developed a futon with a ventilation mechanism and an air-control method that measures the temperature inside the bed and maintains a comfortable temperature (32±2°C) using feedback control. We verified the performance of the temperature control system and evaluated the sleep quality of four participants by measuring PSG (polysomnogram) . The results showed that the in-bed temperature was kept in the “comfortable temperature” zone 99.84% of the time when the subjects were in the bed using the feedback control method developed. We also confirmed the following tendencies: (1) When the air-controlled method was being used, sleep latency was marginally shortened (p<0.1), meaning that the subjects fell asleep more easily; (2) the ratio of “SWS (slow wave sleep, i. e., deep sleep)” significantly increased (p<0.05), indicating that sleep rhythms improved; and (3) the effectiveness of sleep was higher than that of the method without the air-control method. These results indicate that the air-control method developed is effective for increasing the quality of sleep.